A patient-derived orthotopic xenograft (PDOX) nude-mouse model precisely identifies effective and ineffective therapies for recurrent leiomyosarcoma. (April 2019) - Zhang, Zhiying; Hu, Kaiwen; Kiyuna, Tasuku; Miyake, Kentaro; Kawaguchi, Kei; Igarashi, Kentaro; Nelson, Scott D.; Li, Yunfeng; Singh, Shree Ram; Hoffman, Robert M.
Graphical abstract: Abstract: Leiomyosarcoma is a rare and recalcitrant disease. Doxorubicin (DOX) is usually considered first-line treatment for this disease, but frequently is ineffective. In order to individualize therapy for this and other cancers, we have developed the patient-derived orthotopic xenograft (PDOX) mouse model. In the present study, we implanted a recurrent leiomyosarcoma from a resected tumor from the patient's thigh into the femoral muscle of nude mice. The following drugs were tested on the leiomyosarcoma PDOX model: DOX, the combination of gemcitabine (GEM) and docetaxel (DOC), trabectedin (TRA), temozolomide (TEM), pazopanib (PAZ) and olaratumab (OLA). Of these agents GEM/DOC, TRA and TEM were highly effective in the leiomyosarcoma PDOX model, the other agents, including first-line therapy DOX, were ineffective. Thus the leiomyosarcoma PDOX model could precisely distinguish effective and ineffective drugs, demonstrating the potential of the PDOX model for leiomyosarcoma treatment.